A Randomized Trial Evaluating Online 3-Dimensional Optical Frequency Domain Imaging–Guided Percutaneous Coronary Intervention in Bifurcation Lesions. (December 2020) - Onuma, Yoshinobu; Kogame, Norihiro; Sotomi, Yohei; Miyazaki, Yosuke; Asano, Taku; Takahashi, Kuniaki; Kawashima, Hideyuki; Ono, Masafumi; Katagiri, Yuki; Kyono, Hiroyuki; Nakatani, Shimpei; Muramatsu, Takashi; et al.
Abstract : Background: Clinical implications of online 3-dimensional optical frequency domain imaging (3D-OFDI)-guided stenting for bifurcation lesions have not been investigated in the randomized controlled trials. The purpose of this study was to determine whether online 3D-OFDI-guided stenting is superior to angiography-guided percutaneous coronary intervention (PCI) in terms of incomplete stent apposition at the bifurcation segment. Methods: The OPTIMUM trial (Online 3-Dimensional Optical Frequency Domain Imaging to Optimize Bifurcation Stenting Using UltiMaster Stent) was a randomized, multicenter clinical trial. Eligible patients had an angiographically significant stenosis in the bifurcation lesion treated with a provisional single stent strategy using the Ultimaster sirolimus eluting stent. Patients were randomly allocated to either online 3D-OFDI-guided or angiography-guided PCI. Patients randomized to 3D-OFDI guidance underwent online 3D-OFDI assessment after rewiring into the jailed side branch after stenting and proximal optimization technique, while in the angiography guidance arm, rewiring was performed using conventional fluoroscopic/angiographic guidance. The primary end point of this trial was the postprocedural average percentage of malapposed struts per lesion assessed by OFDI in the confluence zone of the main and side branches. Results: Between June 8, 2017 and September 26, 2018, 110 patients with 111 bifurcation lesions were randomized at 4 Japanese centers. Of these, 56 patients with 57 lesions were treated with 3D-OFDI-guided PCI, whereas 54 patients with 54 lesions were treated with angiography-guided PCI. In the 3D-OFDI guidance arm, the feasibility of online 3D-OFDI was 98.2%. The average percentage of incomplete stent apposition per lesion at bifurcation was lower in the 3D-OFDI guidance arm than that in the angiography guidance arm (19.5±15.8% versus 27.5±14.2%, P =0.008). The superiority of the 3D-OFDI guidance arm was also confirmed in the strut level analysis (odds ratio: 0.54 [95% CI, 0.36–0.81]; P =0.003). Conclusions: Online 3D-OFDI-guided bifurcation PCI was superior to angiography-guided bifurcation PCI in terms of acute incomplete stent apposition at bifurcation. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02972489. Abstract : Supplemental Digital Content is available in the text.